AXL antibody and AXL-ADC mediate antitumor efficacy via targeting AXL in tumor-intrinsic epithelial-mesenchymal transition and tumor-associated M2-like macrophage - Pei Jin-peng; Wang Yue; Ma Lan-ping; Wang Xin; Liu Liang; Zhang Yu; Jin Rui; Ren Zhi-qiang; Deng Yan; Shen Jing-kang; Meng Tao; Yu Ker (Acta Pharmacologica Sinica; Vol 44, No 6 (June 2023): Acta Pharmacologica Sinica, 2023)
The receptor tyrosine kinase AXL is an emerging driver of cancer recurrence, while its molecular mechanism remains unclear. In this study we investigated how AXL regulated the disease progression and poor prognosis in non-small cell lung cancer (NSCLC) and triple negative breast cancer (TNBC). We performed AXL transcriptome analysis from TCGA datasets, and found that AXL expression was significantly elevated in NSCLC and TNBC correlating with poor prognosis, epithelial-mesenchymal transition (EMT) and immune-tolerant tumor microenvironment (TME). Knockdown of AXL or treatment with two independent AXL antibodies (named anti-AXL and AXL02) all diminished cell migration and EMT in AXL-high expressing NSCLC and TNBC cell lines. In a mouse model of 4T1 TNBC, administration of anti-AXL antibody substantially inhibited lung metastases formation and growth, accompanied by reduced downstream signaling activation, EMT and proliferation index, as well as an increased apoptosis and activated anti-tumor immunity. We found that AXL was abundantly activated in tumor nodule-infiltrated M2-macrophages. A specific anti-AXL antibody blocked bone marrow-derived macrophage (BMDM) M2-polarization in vitro. Targeting of AXL in M2-macrophage in addition to tumor cell substantially suppressed CSF-1 production and eliminated M2-macrophage in TME, leading to a coordinated enhancement in both the innate and adaptive immunity reflecting M1-like macrophages, mature dendritic cells, cytotoxic T cells and B cells. We generated a novel and humanized AXL-ADC (AXL02-MMAE) employing a site-specific conjugation platform. AXL02- MMAE exerted potent cytotoxicity against a panel of AXL-high expressing tumor cell lines (IC50 < 0.1 nmol/L) and suppressed in vivo growth of multiple NSCLC and glioma tumors (a minimum efficacy dose